Tears of Biceps Femoris, Semimembranosus, And Semitendinosus are Not Equal—A New Individual Muscle-Tendon Concept in Athletes - Lempainen Lasse; Kosola Jussi; Pruna R; Sinikumpu JJ; Valle X; Heinonen Olli J; Orava Sakari; Mafulli N (United Kingdom, 2022)
Objectives: Hamstring injuries are common and can now be accurately diagnosed. In addition, novel surgical indications have been introduced. However, evidence-based guidelines on the hamstring injuries in management of top-level athletes are missing.
Methods: The management methods and outcomes of treatment are classically based on relatively small case series. We discuss a novel concept based on the fact that each tendon of the hamstrings muscle should be managed in an individual fashion. Furthermore, suitable indications for hamstring surgery in athletes are introduced.
Results: The present study introduces modern treatment principles for hamstring injury management. Typical clinical and imagining findings as well as surgical treatment are presented based on a critical review of the available literature and personal experience.
Conclusion: Hamstring injuries should not be considered to be all equal given the complexity of this anatomical region: The three separate tendons are different, and this impacts greatly on the decision-making process and outcomes in athletes.